Dinamika Pasar Minyak Dan Gas Bumi: Implikasinya Terhadap Keseimbangan Ekonomi Global - Edy Soesanto; Citra Wahyuningrum; Mohammad Ikbar Fikri Rosyada (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This research uses literature study analysis to evaluate the influence of oil and gas exports, non-oil and gas exports and foreign investment on Indonesia's economic growth. The results show that dependence on the oil and gas sector has a negative impact on economic growth, while growth in non-oil and gas exports and foreign investment has a positive impact. Economic diversification through increasing non-oil and gas exports and appropriate foreign investment can reduce dependence on the oil and gas sector and increase Indonesia's economic resilience. However, keep in mind that the interaction between these variables is not always linear and can affect overall economic growth.